Influence of the focusing characteristics of near-infrared lasers on the maintenance of plasma luminescence - Zhou, Lian; Chen, Yi; Guo, Xin; Shi, Yan; Zhao, Tianqi; Zhan, Chunlian; Jin, Shangzhong (Frontiers in Physics, 2022)
The interaction of 980 nm continuous laser radiation with plasma of a continuous optical discharge in xenon at a pressure of p=12 atm has been studied. The threshold power and its characteristics of laser required to sustain a xenon plasma become our focus. According to the theory of Gaussian beam propagation, the laser parameters after collimation and focusing are obtained by combining ZEMAX simulation and actual measurement. The influence of beam waist ω0, which determines the power density distribution at the focus, and Rayleigh range Z0, which determines the energy concentration range, on the threshold maintenance power is expounded. The results show that there is a threshold power density for the generation of plasma, this value is about 1500 2000 W/mm2, and that the threshold maintenance power of the plasma shows an overall decreasing trend with decreasing ω0. When ω0 continues to decrease to the point where a higher power density can easily maintain the thermodynamic equilibrium process of the plasma, the mismatch between Z0 and the plasma size caused by the decrease of Z0 makes the threshold power tend to be stable and increase.